Kinetics of bainite precipitation in the Cu69.3Al18.8Mn10.3Ag1.6 alloy - Motta, M. B.J.L.; Adorno, A. T. [UNESP]; Santos, C. M.A. [UNESP]; Silva, R. A.G. (Elsevier, 2017)
In this work the kinetics of bainite precipitation in the Cu69.3Al18.8Mn10.3Ag1.6 alloy was studied using measurements of microhardness change with aging time, scanning electron microscopy (SEM), energy dispersive X-ray (EDX) analyses, measurements of magnetization change with applied field and high-resolution transmission electron microscopy (HRTEM). The results showed that the bainite precipitation is responsible for the hardness increase in the Cu69.3Al18.8Mn10.3Ag1.6 alloy. The activation energy value obtained for the bainite precipitation is lower than that found in the literature. This was attributed to the presence of Ag dissolved in matrix and the occurrence of the Cu3Al(DO3) → Cu2AlMn(L21) ordering reaction together with the bainite precipitation.
Keywords: Aging; Kinetics; Metals and alloys